Penerapan Neuro Linguistic Programming (Nlp) dalam Kecerdasan Emosional untuk Keberhasilan Siswa - Asep Sutisna Sanjaya (Jurnal Syntax Transformation, 2022)
The purpose of these best practices is to find truth through the application of neuro linguistic programming in emotional intelligence can increase student success. The result in this best practice is qualitative results or effects of successful changes in behavior in students, and the quantitative measure of success in the academic field which is the influence of the application of neuro linguistic programming in emotional intelligence of students. C who is a student who teaches himself every day. Conducted at Pisangan Baru SDN 01, located precisely on Jalan Jendral Ahmad Yani No. 30 Pisangan Baru Village, Matraman District, East Jakarta Administrative City. With the application of neuro linguistic programming in emotional intelligence students have results qualitatively (1) More who they are, where they are, and where they want to be (2) Having the meaning of life (3) Knowing what their goals are and what to do (4) Tau how to treat the people around him, his friends, his younger siblings, his teacher, his parents and even other people he met (5) more sensitive to what is happening around him (6) more meaningful life, while quantitatively there is an increase in learning outcomes with an average Natural Knowledge Score 73.70 which previously averaged 63.20.